Value in Single-level Lumbar Discectomy: Surgical Disposable Item Cost and Relationship to Patient-reported Outcomes. Issue 9 (November 2017) - Rosenbaum, Benjamin P.; Modic, Michael T.; Krishnaney, Ajit A.
Abstract : Study Design: This is a retrospective study. Objective: Compare improvements in health status measures (HSMs) and surgical costs to determine whether use of more costly items has any relationship to clinical outcome and value in lumbar disc surgery. Summary of Background Data: Association between cost, outcomes, and value in spine surgery, including lumbar discectomy is poorly understood. Outcomes were calculated as difference in mean HSM scores between preoperative and postoperative timeframes. Prospective validated patient-reported HSMs studied were EuroQol quality of life index score (EQ-5D), Pain Disability Questionnaire (PDQ), and Patient Health Questionnaire (PHQ-9). Surgical costs consisted of disposable items and implants used in operating room. Methods: We retrospectively identified all adult patients at Cleveland Clinic main campus between October 2009 and August 2013 who underwent lumbar discectomy (652) using administrative billing data, Current Procedural Terminology (CPT) code 63030. HSMs were obtained from Cleveland Clinic Knowledge Program Data Registry. Results: In total, 67% of operations performed in the outpatient or ambulatory setting, 33% in the inpatient setting. Among 9 surgeons who performed >10 lumbar discectomies, there were 72.4 operations per surgeon, on average. Mean surgical costs of each surgeon differed ( P <0.0001). In a multivariable regression, only the surgeon and surgery type (outpatient or inpatient) were statistically correlated with surgical costs ( P <0.0001 and 0.046, respectively). Changes in EQ-5D, PDQ, and PHQ-9 were not correlated with surgical costs ( P =0.76, 0.07, 0.76, respectively). In multivariable regression, only surgical cost was significantly correlated to mean difference in PDQ ( P =0.030). More costly surgeries resulted in worse PDQ outcomes. Conclusions: Mean surgical costs varied statistically among 9 surgeons; costs were not shown to be positively correlated with patient outcomes. Performing an operation using more costly disposable supplies/implants does not seem to improve patient outcomes and should be considered when constructing preference cards and during an operation.